1932
DOI: 10.1007/bf02553782
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide formation as a measure of autoxidative deterioration

Abstract: Summary 1. A brief review of the literature of rancidity, especially methods of detecting and determining rancidity is given. 2. A rapid and convenient method of determining peroxides or “active oxygen” in vegetable oils has been developed. 3. A study of peroxide formation in cottonseed and corn oils at 100° C. was made. The relation of peroxide concentration to iodine number, oil color, and intensity of Kreis color is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

1941
1941
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(66 citation statements)
references
References 21 publications
0
65
0
1
Order By: Relevance
“…These effects include the emulsifier-associated increased w/o-interface and the possible complex formation between anthocyanins and emulsifier molecules which altered the lipophilicity and the w/o-partition coefficient of the anthocyanins. A low peroxide value (Wheeler, 1932), i.e. a low oxidation status of the sunflower oil was determined, which was not changed during the microencapsulation process (data not shown).…”
Section: Influence Of Emulsification and Emulsifier Addition On The Amentioning
confidence: 99%
“…These effects include the emulsifier-associated increased w/o-interface and the possible complex formation between anthocyanins and emulsifier molecules which altered the lipophilicity and the w/o-partition coefficient of the anthocyanins. A low peroxide value (Wheeler, 1932), i.e. a low oxidation status of the sunflower oil was determined, which was not changed during the microencapsulation process (data not shown).…”
Section: Influence Of Emulsification and Emulsifier Addition On The Amentioning
confidence: 99%
“…Flavored oils were held for 48 h at 60°C and, afterwards, the peroxide value was determined by Wheeler's method [16].…”
Section: Determination Of Peroxide Valuementioning
confidence: 99%
“…50 g Woelm neutral or, preferably, alkaline (cationotropic) alumina. An iodometric estimation of peroxides by Wheeler's (1932) method has shown that distillation alone reduced these to 2 *LM/l. and further passage through alumina to 1 ,uM/l.…”
Section: Investigation Of An Active Lipid In Aqueous Extracts Of Rabbmentioning
confidence: 99%